Policy options for the development of peripheral regions and countries of Europe - Karl Aiginger; Peter Huber; Matthias Firgo (WWWforEurope, 2012)
Given the recent economic problems of southern EU countries that are rooted in lacking competitiveness, this task will summarise existing knowledge on the factors impeding on or facilitating the economic development of peripheral/low income regions in the EU, and discuss policy options to improve economic performance of Southern european countries while at the same time maintaining (or improving) sustainability. In the light of recent developments a central focus will be put on Greece, Italy, Portugal and Spain, and on the question of how national, community wide policies and spillovers from the centre can contribute to the double objective of improving competitiveness and sustainability in these countries. A substantial part of the empirical evidence for the policy conclusion comes from anylyzing the catching up experience of regions within countries, since this situation resembles the chances and problems of countires catching up within a Monetary Union (without the possibility to improve competitiveness and correct policy failures by devaluations). The results of this task will be reported in a separate deliverable (in the form of a policy brief) and will serve the researchers involved in all tasks of this work package as a starting point for further analysis.
Keywords: R11; E60; 330; Competitiveness; economic growth path; European economic policy; labour markets; peripheral areas; rural areas